2022
DOI: 10.3390/healthcare10112228
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers and Facilitators to Psychotherapy Utilisation and How They Relate to Patient’s Psychotherapeutic Goals

Abstract: Access to psychotherapy is still limited by various barriers, and little is known about the facilitating circumstances. This study aims to assess self-reported barriers and facilitators to psychotherapy utilisation in private practice and how these access factors relate to psychotherapy goals as formulated by patients. The dataset consists of 21 face-to-face semi-structured interviews with patients treated by psychotherapists in private practice in Austria. Data were analysed using qualitative content analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Sheffield et al [ 25 ] showed that, among other barriers, adolescents mostly found seeking professional help too expensive, did not know where to find it, or perceived it as too far away. In Austria, unaffordability and confusion about the workings of the funding system were also found to be critical external barriers to seeing a psychotherapist [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sheffield et al [ 25 ] showed that, among other barriers, adolescents mostly found seeking professional help too expensive, did not know where to find it, or perceived it as too far away. In Austria, unaffordability and confusion about the workings of the funding system were also found to be critical external barriers to seeing a psychotherapist [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using a semi-structured qualitative interview approach ( 52 ), therapists and patients share their experiences by answering reflective and open-ended questions face-to-face with interviewers recruited from psychotherapy students at the UWK. The interview guide, designed for both patients and psychotherapists by BS, YS, and AJ, starts with motivations at the beginning of therapy ( 66 ). It explores the evolution of therapy goals from start to present and prompts reflection on pivotal moments and impactful dialogues within the therapeutic process.…”
Section: Design and Methodsmentioning
confidence: 99%
“…These maps aim to capture and reflect the diverse practices and experiences related to the phenomena under study ( 67 ). For instance, this approach enables us to explore variations in how patients seek therapists in private practice ( 66 ) or their views and experiences with therapists of the same or opposite gender. We also closely examine therapists’ perspectives, including their views and experiences with interventions or what patients and therapists find helpful at different stages.…”
Section: Design and Methodsmentioning
confidence: 99%
“…Moreover, while it is true that therapists’ positive attitudes and beliefs about psilocybin have been associated with greater openness to involving patients with psilocybin-assisted psychotherapy [ 74 ], potential limitations in terms of accessibility to care can be anticipated. For example, as noted by some authors, economic and other treatment engagement issues can act as barriers to receiving psychotherapy assistance, particularly in poorer populations and minority groups [ 75 , 76 , 77 , 78 ].…”
Section: Challenges Limitations and Suggestionsmentioning
confidence: 99%